As principais estratégias utilizadas pela gestão da agência do SICREDI de Campo Bom para impulsionar o crescimento da mesma. - Bellé, Fernanda Cézar (Universidade do Vale do Rio dos Sinos, 2017)
The Sicredi agency of Campo Bom has been in business since 2011 and since then has a distinguished performance within the cooperative to which it belongs. This article has as general objective to identify the main strategies used by the management of this agency that have impulse its growth. For this purpose, the Sicredi Nordeste cooperative, Campo Bom agency, the development of the portfolio, the results and the indexes of the agency are presented. The theoretical reference presents management and strategic planning concepts and information about its stages of development. In addition, it presents data about cooperativism and its main characteristics. About the methodology, it is considered a case study and a documentary and participant research, besides being qualitative and descriptive. To obtain the necessary information for the development of this article, interviews with employees of the company were applied and consultation to the internal documents, besides the other baseline researches for the theoretical reference. In front of the presentation of the agency's data, it is possible to identify the strategy directed to some specific products that generate more revenue and are more representative in the proposed objective, which is the positive liquid and operating result.
Keywords: Estratégia; Cooperativismo; Crescimento de carteira; Strategy; Cooperativism; Portfolio growth